PENYELENGGARAAN PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH KUANTAN SINGINGI - Amalia, Rizki; Meilani, Nur Laila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The implementation of health services carried out at the Kuantan Singingi Regional General Hospital where the implementation of health services there are problems with the doctor's slow coming, waiting for the medicine to be treated for a long time, sometimes there is no medicine so it requires buying outside, the doctor is not there and there is no substitute doctor, the officers are less friendly registration. The purpose of this study is to Organize Health Services at the General Hospital of Kuantan Singingi and find out the factors that influence the Implementation of Health Services at the General Hospital of Kuantan Singingi.Using the concept of public service theory according to Suryadi (2009: 69). Using qualitative descriptive methods. The type of data used is primary data and secondary data. Data collection uses observation, interview, literature study, documentation. Data analysis used is data reduction, data presentation, conclusion drawing and verification. The results of the study addressing the Implementation of Health Services at the General Hospital of Kuantan Singingi, the hospital has not run optimally. The factors that influence the Implementation of Health Services in the General Hospital of Kuantan Singingi, are the Facilities and Infrastructure and Respom of Officers that are Poor Keywords: Service, Health, Hospital